Reaction synthesis and mechanical properties of B4C-based ceramic composites - Han, Jae-Ho; Park, Sang-Whan; Kim, Young-Do (PROGRESS IN POWDER METALLURGY, PTS 1 AND 2, 2007)
Boron carbide is a very hard material with high abrasive wear resistance. It requires a very high sintering temperature of above 2200 degrees C to fabricate a monolithic B4C close to the theoretical density. However, the mechanical property of monolithic B4C is not good enough to use it directly to industrial applications. In this investigation, B4C based ceramic composites were fabricated by in-situ reaction hot pressing using B4C, TiC and SiC powder as starting materials. The reaction synthesized composites by hot pressing at 1950 degrees C was found to posses very high relative density. The reaction synthesized B4C composites comprise B4C, TiB2, SiC and graphite by the reaction between TiC and B4C. The newly formed TiB2 and graphite was embedded both inside grain and at grain boundary of B4C. The mechanical properties of reaction synthesized B4C-TiB2-SiC-graphite composites were more enhanced compared to those of monolithic B4C. The flexural strength and fracture toughness of these in-situ B4C synthesized composites were 400-570 MPa and 6-9.5 MPam(1/2), respectively.